Quasi-static analysis and modeling for micro ohmic contacts in MEMS switches - See, Raymond Seng Hong. (2011)
Microelectromechanical Systems (MEMS) have been developed since the 1970s for pressure and temperature sensors, accelerometers, gas chromatographs and other sensor devices. In the recent versions of Nintendo’s Wii, MEMS plays an important part to allow the Wii controller to respond to changes in direction, speed and acceleration. MEMS switches have also been demonstrated in the early 1980s but remained a laboratory curiosity for a long time. RF MEMS switches offer a high-performance, low power, low-cost alternative to traditional diode switches. RF MEMS technology is now at a turning point and reliability issues are currently been addressed. Contact analysis and modeling of ohmic MEMS switches is one of most crucial reliability studies to be performed.